PENGARUH BOOK TAX DIFERRENCE YANG DIUKUR DENGAN FIXED ASSETS, SALES GROWTH DAN DEFERRED TAX EXPENSE TERHADAP TAX AVOIDANCE : (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021) - Ida Indriani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study is to find out how Book Tax Difference as measured by the ratio of Fixed assets, Sales growth and Deffered tax expenses affects the possibility of Tax avoidance in Manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 – 2021. The research method used is a descriptive research method and verification analysis.The population in this study consisted of manufacturing companies listed on the Indonesia Stock Exchange. Sampling in this study was carried out by purposive sampling technique. There are 14 manufacturing companies that meet the criteria to be used as research samples.The analytical method used is Multiple Linear Regression analysis. Based on the results of the study using analysis of the coefficient of determination, it shows that partially the variable that has the most influence on the Tax avoidance variable is the Sales Revenue variable (X2) of 15.4% and followed by the Deffered tax expense variable of (X3) of 15.1% and the Fixed variable Assets (X1) of 13.1%. Thus the overall effect is 43.6% while the remaining 56.4% is contributed by variables other than Fixed assets, Sales growth, and Deffered tax expenses. Based on the output results using SPSS 16.0, the coefficient of determination can be obtained, which is equal to 0.436. This means that simultaneously Fixed assets (X1), Sales growth (X2), and Deffered tax expenses of (X3) affect Tax avoidance (Y) of 43.6 % while the remaining 56.4% is influenced by other factors not examined in this study.